Emina Girl Gang Ambassador (EGGA) As A Public Relations Marketing Strategy in Building Emina Cosmetic’s Brand Image - Devyna Chintya Dewi; Yuliana R. Prasetyawati; Jhevo Adiprasetiya Akbar (Universitas Pendidikan Ganesha, 2021)
Cosmetics are ingredients that are used to support one's appearance and at the same time have a good impact on the health of the human body. Nowadays, cosmetics are not only used for aesthetic effect, they also increase self-confidence and look more attractive. The steadily increasing growth of the local cosmetics business sector in Indonesia has become a subject of attention for PT Paragon Technology and Innovation which is a cosmetics company that owns three main brands: Make Over, Wardah and Emina Cosmetic. In this study, the researcher intends to discuss in depth Emina of PT paragon through the best strategy to maintain a firm presence in the competitive business of local cosmetics. Certainly, Effective and creative strategies are. Without a doubt, needed so that the company can compete on attracting public attention, one of these strategies is the application of Emina Girl Gang Ambassador (EGGA) as a Public Relations Marketing strategy in the company. Through this study, the researcher intends to determine and analyze the role of Emina Girl Gang Ambassador in 7 Marketing Public Relations tools by Kotler and Keller. This study used a descriptive qualitative method with data collection techniques of semi-structured interviews and data reduction analysis techniques by Miles and Huberman. The results showed that Emina's brand from PT Paragon Technology and Innovation used 2 main tools from 7 points presented by Kotler and Keller, namely events and sponsors.